Pengaruh Variasi HA-TCP (Hydroxy Apatit-Tricalcium Pospat) Terhadap Biokomposit (HA:TCP)-Gelatin-CMC Sebagai Injectable Bone Subtitute (IBS) - Purwiandono, Gani; Julita, Hera; Saputra, Dita Adi (Chemistry Department, Universitas Islam Indonesia, 2018)
The synthesis of biocomposite (HA:TCP) – Gelatine – CMC for bone filler material has been carried out. In this research, the ratio of HA and TCP was varied as follows: 70:30, 50:50 and 40:60. The decrease of HA and the increase of TCP concentration will decrease the density, increase the percentage of porosity and swelling. The best composition for the synthesis was obtained for sample B with the ratio of HA:TCP = 50:50. For sample B, the synthesized biocomposite has the density of 1.67790 gr/cm3, porosity of 78.64%, tension of 10.14 MPa, swelling ability 46.85% and the sample mass degradation percentage of 8.1 %. The composition used for the biocomposite synthesis in this research was suitable to be applied as bone filler material which needs a dense pores and high tension.